The Estimation of Quality-Adjusted Auction Returns with Varying Transaction Intervals - Taylor, William M. (Journal of Financial and Quantitative Analysis, 1992)
Previous research has separately addressed the problem of estimating risk in the presence of infrequent trading and the problem of estimating quality-adjusted returns in markets with quality variation in the observed price series. This paper simultaneously addresses both problems by applying a signal extraction method for unequally spaced data to decompose the observed price series with varying times between transactions into a quality-adjusted, permanent component (which would be observable in the absence of quality variation) plus a stationary, transitory quality variation component. Stamp auction transaction prices provide an application. Auction quality grading is treated in a manner analogous to bond ratings. Almost all of the observed variance is attributed to the auction quality variation. The observed auction returns and stock index returns are not well related.